THE EDUCATION AND SOCIALIZATION CONCEPT OF THE DEFENDANTS IN RUSSIAN CORRECTIONAL INSTITUTIONS - Vyacheslav T. Volov; Vsevolod V. Volov (Образование и наука)
Article retractedThe aim of the research is to present the authors’ rehabilitation and development concept of identity of the defendant. Modern penal system instead of resocialization initiates person desocialization, i.e. isolation of the people who have offended against the law, does not promote their rehabilitation and reeducation. Due to external macro-isolation the defendant at all desire can not be isolated from criminogenic micro-society of the custodial institution, where he/she serves the sentence. Long stay in such position often leads to destruction of the person’s standard-valuable sphere and recidivism of asocial behaviour. Providing defendants with possibility of distant vocational training in a higher educational institution as one of the possible variants of positive socialization in extreme conditions of the restraint is given by the authors of this paper. Methods. Longitudinal method has been used during the long experiment on defendants’ socialization providing them with higher education. Quantitative measures have been carried out on the basis of monitoring and the statistic data of comparative analysis of its standard-valuable characteristics of the trainable and non-trainable defendants. Expert estimations of correctional officers and teachers or tutors of the higher school (the Modern University for the Humanities) and in-depth interviews with former defendants ended high school have been used too. Results and scientific novelty. The phenomenon essence of penal isolation is found out. The external and internal factors defining the process of defendants’ socialization/desocialization in correctional institution are mentioned. Religion and penal education are highlighted as the most effective and positive factors. The principles of person’s rehabilitation on the basis of getting higher education by defendants are formulated: the extremity principle, the congruence principal, the balance principle between the personal isolation and social communication. The compensatory mechanism of social-psychological defendant’s alienation and the innovative mechanism of process management of their positive socialization are described. The authors of the research present the results of their own program realization for the prisoner’s socialization that has successfully passed approbation in 33 correctional institutions of the Samara region. Practical significance. The authors of the present study hope that their experience on overcoming of socially-psychological barriers of defendants’ socialization, corrections of their behaviour, preventive maintenance of criminal displays recidivism will receive more a widespread occurrence and will allow the persons serving the sentence to gain an opportunity of a worthy life in the society.